Analisis Du Pont System (ROI, NPM DAN TATO) Dalam Mengukur Kinerja Keuangan Perusahaan Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019 - Triana Zeni Andianti; Setio Utomo; Novia Nour Halisa (Business Administration, FISIP ULM, 2022)
ABSTRACT : This study aims to conduct a Du Pont System analysis (ROI, NPM and TATO) in measuring the financial performance of telecommunications companies listed on the Indonesia stock exchange for the 2015-2019 period. The research approach uses quantitative, with the type of research the comparative-associative. Samples were taken of all components in the form of company data, namely telecommunications company financial data that measures the value of NPM (Net Profit Margin), TATO (Total Assets Turnover) and ROI (Return On Investment) 2015-2019, census sampling technique / total sampling. Data collection used secondary data with documentation study, while data analysis used descriptive statistical analysis and two way ANOVA. The results prove that H1 is rejected, meaning that there is no difference in the financial performance of telecommunications companies 2015-2019 based on financial ratio grouping, with a sig. 0.86. H2 is accepted, meaning that there is a difference in the financial performance of telecommunications companies for 2015-2019 based on grouping of business entities (companies), with a sig. 0.45. And H3 is accepted, meaning that there is a du pont system interaction with telecommunications companies in the financial performance of telecommunications companies 2015-2019, with a sig value of 0.021. Keywords: ROI, NPM, TATO, Financial Performance